Pharmacy Students' Perceptions of a Required Senior Research Project - Kim, Sylvia E. (American Journal of Pharmaceutical Education, 2010)
OBJECTIVES: To determine pharmacy students' perceptions of a required research project in a doctor of pharmacy curriculum. METHODS: A survey instrument was administered to senior pharmacy students to determine their perceptions of the project advisor and overall project experience and their postgraduation employment plans. RESULTS: Two-hundred twenty-nine (81.5%) students completed a survey instrument. The majority agreed or strongly agreed that the project provided a valuable learning experience (88.2%), provided a competitive advantage for postgraduate job opportunities (73.2%), and should be a continued graduation requirement (74.2%). Respondents with plans for a residency or fellowship were more likely than those entering a community or hospital/institutional pharmacy to agree that completion of the project made them more qualified or marketable and should be continued as a graduation requirement (p < 0.05). CONCLUSIONS: A required research project was perceived by pharmacy students to be a beneficial experience. Students pursuing residency or fellowship were more likely to feel the project was beneficial than students entering the workforce.